War transformed the future of twenty-first-century great power competition and conflict - Ryan, Mick 1969- (Naval Institute Press, 2022)
"War Transformed provides insights for those involved in the design of military strategy, and the forces that must execute that strategy. Emphasizing the impacts of technology, new era strategic competition, demography, and climate change, Mick Ryan uses historical as well as contemporary anecdotes throughout the book to highlight key challenges faced by nations in a new era of great power rivalry"--
Keywords: Strategie; Kriegführung; Militärwissenschaft; War / Forecasting; Military art and science; Strategy; World politics / 21st century; Military Science; Guerre / Prévision; Art et science militaires; Stratégie; Politique mondiale / 21e siècle; World politics; 2000-2099